Wireless Monitoring of Urban Wind Turbines by ZigBee Protocol: Support Application Software and Sensor Modules - Batista, Nelson (2015)
This paper is about wireless monitoring of an urban vertical axis wind turbine, focusing on the layered system used for the computational framework of sensors, data acquisition, data processing and storage system interconnectivity. A low power wireless networks employing ZigBee protocol is used for the sensors modules connectivity. A voltage and current sensor and an infrared photoelectric sensor developed for the monitoring are succinctly described. The usability in a Smart Grid environment were taken in consideration in the design of the modules, wireless networks creation and the computation engineering.